Pediatric Germ Cell Tumors: An Experience of 7 Years in a Tertiary Hospital of Bangladesh - Kabir, SM Rashed Zahangir; Akhtar, Md Waheed; Yasmin, Farida (Dhaka Shishu (Children) Hospital Journal, 2020)
Introduction: Germ cell tumors are a group of tumors with different clinical presentation and histological and biological characteristics. Malignant germ cell tumors occur at all ages with a trend of bimodal distribution in infancy and adolescence. Objective: To evaluate the demographic characteristics, distribution of different types of germ cell tumor, treatment modalities and outcome of germ cell tumor in children in a tertiary care hospital of Bangladesh. Methods: In this retrospective study, data regarding age and sex distribution, location, types of tumors, management of germ cell tumor in children were retrieved from the medical records of pediatric oncology department in NICRH, Dhaka from 2008 to 2014. Results: Out of total 87 patients female were 50 and male 37. Most of the patients were up to 5 years of age. The gonadal germ cell tumors (80%) were more than extragonadal tumor (20%) in both male and female patients. The most common germ cell tumor was dysgerminoma (32%) followed by yolk sac tumor (29.8%) and teratoma (19.5%). Yolk Sac Tumor (51.4%) was the most common in male and dysgerminoma (56%) the commonest in female. Out of 87, seventy two (82.7%) received chemotherapy following surgery. Among those 72 patients who received chemotherapy 49 (68 %) patients completed their treatment. Until the last follow up 71.4% patients remained alive and tumor free. Conclusion: Germ cell tumors are the most variable tumor of all childhood malignancies that has difference in age, sex, location and histological subtypes. Gonadal tumors have better prognosis than extragonadal tumors in both the sex. DS (Child) H J 2019; 35(2) : 119-122